Mathematics for business, science, and technology [ with MATLAB and spreadsheet applications - Karris, Steven T. (Orchard Publications, 2007)
This text is targeted at high school seniors who plan to enter business, science, and technology related fields, and working professionals seeking to enhance their knowledge on various math topics including probability and optimization methods. This book begins with the basic mathematical operations and ends with advanced and yet practical examples. Contains many real-world examples supplemented with computer applications. It is ideal for self-study.